Acute oral and dermal toxicity parameters of a drug based on D-cyphenothrin, pyriproxyfen and piperonyl butoxide in laboratory animals - M. V. Arisov; E. N. Indyuhova; G. B. Arisova; D. S. Poselov; A. A. Stepanov; E. V. Poselova (Российский паразитологический журнал, 2024)
The purpose of the research is to study acute oral and dermal toxicity parameters of a drug based on D-cyphenothrin, pyriproxyfen and piperonyl butoxide in laboratory animals.Materials and methods. The study insectoacaricidal drug contains D-cyphenothrin, pyriproxyfen, piperonyl butoxide, hydrogenated castor oil and isopropyl alcohol. The acute toxicity parameters of the drug in 5% solution formulation were studied on 50 white outbred male mice when administered intragastrically, and on 42 outbred male rats when administered orally and on skin. The acute toxicity parameters were calculated using the Litchfield and Wilcoxon method as modified by Z. Rotha, and the drug exposure value on the body was evaluated as per the established classification (GOST 12.1.007). Results and discussion. The following toxicological characteristics were obtained: LD50 of the study drug administered orally to the white mice was 2,656 (2,207.8÷3,187.2) mg/kg, and the white rats, 5,063 (4482÷5818.3) mg/kg. The maximum tolerated dose of the drug was 830 mg/kg for the mice, and 2,075 mg/kg for the rats. Based on the obtained LD50 values, the three-component insectoacaricide can be classified as hazard category 3 (moderately hazardous substances) in experiments on mice, and hazard category 4 (marginally hazardous substances) on rats pursuant to the established hygienic classification. At the same time, different species sensitivity to the drug can be observed in mice and rats. LD50 was more than 30,710 mg/kg in the study of dermal toxicity on the white rats, therefore the drug can be classified as hazard category 4.